Impact of COVID-19 on the elderly (Journal of Patan Academy of Health Sciences, 2020)
While in most developed countries an adult of age 65 years and above is considered an elderly, in Nepal, its 60 years. There will be two billion people in old age category worldwide by 2050. This rise in number of ageing group presents many challenges; one such challenge was faced during the Corona Virus Disease 2019 (COVID- 19) pandemic. The aim of this narrative review is to assess the impact of COVID-19 on different aspects of life of the elderly. The impact of COVID-19 on the health of the elderly is greater compared to other age groups. Studies from around the world have showed that the risk of severity for COVID-19 is higher among the elderly. Many elderlies who got infected or died were healthcare personnel working in the frontline. Measures like physical distancing, movement restriction and home quarantine, all contributed to the increase in social isolation, especially for the elderly. This in turn could cause problems with their physical, mental, and cognitive health. Additionally, lack of a steady source of income and insufficiency of savings, many face financial crises. Despite efforts to help the old people, they have been enduring the harsh outcomes of the pandemic. To support and respect elderly their dignified life, a clear policy interventions and proper implementations are a must.